2022
DOI: 10.1155/2022/6561633
|View full text |Cite|
|
Sign up to set email alerts
|

Acupuncture for Knee Osteoarthritis: A Systematic Review of Randomized Clinical Trials with Meta-Analyses and Trial Sequential Analyses

Abstract: Background. Knee osteoarthritis (KOA) can cause chronic pain and seriously affect the quality of patient lives. The continued emergence of high-quality RCTS requires us to update the quality of evidence. This study aims to evaluate the efficacy of acupuncture for KOA patients and calculate the required information size (RIS) to determine whether further clinical studies are required. Methods. We searched PubMed, Embase, WOS, CBM, CNKI, VIP, WHO ICTRP, ChiCTR, and Grey literature to collect randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 46 publications
1
20
0
1
Order By: Relevance
“…Compared to other CIM interventions, our study interventions have shown similar (and in part, greater) effects on the WOMAC Index than other CIM interventions; e.g., acupuncture, leeches, and Tai Chi [ 38 , 39 , 40 , 41 , 42 ]. Direct comparisons with the results of this study are possible only to a limited extent, because other studies differed in part fundamentally from the present study in terms of study designs, intervention, and implementation.…”
Section: Discussionmentioning
confidence: 59%
“…Compared to other CIM interventions, our study interventions have shown similar (and in part, greater) effects on the WOMAC Index than other CIM interventions; e.g., acupuncture, leeches, and Tai Chi [ 38 , 39 , 40 , 41 , 42 ]. Direct comparisons with the results of this study are possible only to a limited extent, because other studies differed in part fundamentally from the present study in terms of study designs, intervention, and implementation.…”
Section: Discussionmentioning
confidence: 59%
“…Trials to prove the effectiveness of acupuncture in the treatment of pain is and will be the focuses of this research field. [88][89][90][91][92] The current burst keywords include impact, symptom, depression and stress, indicating that researchers are currently paying more attention to the psychological problems caused by CP. This shows that in recent years, researchers have gradually shifted from simply focusing on chronic pain to secondary symptoms of psychological problems caused by chronic pain, such as depression and stress.…”
Section: Discussionmentioning
confidence: 99%
“…료 효과를 나타내며 1) , 근골격계 질환에서는 통증을 완 화하고, 관절 가동범위를 개선하여 환자의 삶의 질을 높 여주는 효과가 있다 [2][3][4] . 최근에는 조작 방법을 발전시켜 전통 침술에 전기 치료, 열 자극, 약물 치료 등을 접목시 킨 전침 5) , 화침 6) , 매선 요법 7) , 약침 8) 등이 개발되어 임 상에서 응용되고 있다.…”
Section: 전종혁⋅우현준⋅하원배⋅금지혜⋅한윤희⋅박신혁⋅이정한unclassified